If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 4 + 9 = 3x + -2 + 13 Reorder the terms: 4 + 9 + X = 3x + -2 + 13 Combine like terms: 4 + 9 = 13 13 + X = 3x + -2 + 13 Reorder the terms: 13 + X = -2 + 13 + 3x Combine like terms: -2 + 13 = 11 13 + X = 11 + 3x Solving 13 + X = 11 + 3x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + X = 11 + -13 + 3x Combine like terms: 13 + -13 = 0 0 + X = 11 + -13 + 3x X = 11 + -13 + 3x Combine like terms: 11 + -13 = -2 X = -2 + 3x Simplifying X = -2 + 3x
| 4(ax-c)=bx+3d | | -38.46+3.7a=5.5(1+2.1a) | | 5w^2=-21w-4 | | 9x+y=90 | | 2.6666*5= | | 24=2y-4 | | 4(2x+3y)+2(5y+3x)=0 | | 2.6666666*5= | | 5x+61=180 | | 8(2w-1)-4w=80 | | 8w(2w-1)-4w=80 | | (3z+5)(9+z)=0 | | -500=x^2-x | | 2z-15=1+4z | | -2(-w+11)=-13+12w-9 | | 18x=-6y | | z=-4a+5i | | 18x=6y | | 13=9x+1-3x | | 8x+10x=-2(x-2)+3 | | 5m+5=2(m+2)+m+1 | | graphx+2y=10 | | (3x+6)+(x-10)+(x-11)=180 | | .02f+0.6(f+20)=-8+0.4f | | Y+6=-4(x-4) | | 6n-60=0 | | 24=-4(3w+3) | | 2y=-4x-6 | | 6[x-1]=9[x-4] | | -10n+12=-3n-9 | | 3c+15-2=2c+12+2 | | 4y-3x=24 |